Sustainable Products Life Cycle Assessment, Risk Management, Supply Chains, Eco-Design - Has, Michael 1959- (De Gruyter Textbook, 2022)
Sustainable production presented from an overarching perspective. The book provides information on the identification and assessment of footprints, concepts of sustainability practice in manufacturing companies, stakeholder management and communication. For the reader practical examples permit the analysis of the current situation and emerging developments. the current technical status of footprint analysis according to the Green House Gas Protocol is displayed. case studies with a focus on the manufacturing industry are discussed